2020
DOI: 10.1126/science.abc0322
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito cellular immunity at single-cell resolution

Abstract: Hemocytes limit the capacity of mosquitoes to transmit human pathogens. Here we profile the transcriptomes of 8506 hemocytes of Anopheles gambiae and Aedes aegypti mosquito vectors. Our data reveal the functional diversity of hemocytes, with different subtypes of granulocytes expressing distinct and evolutionarily conserved subsets of effector genes. A previously unidentified cell type in An. gambiae, which we term “megacyte,” is defined by a specific transmembrane protein marker (TM7318) and high expression o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 35 publications
9
101
4
Order By: Relevance
“…Next, to demonstrate the power of this feature across species, we compared Drosophila blood marker genes [6] with marker genes derived from A. gambiae (mosquito) blood scRNA-seq [17] . Of note, Drosophila blood cluster ‘PM2′ significantly correlated to ‘HC4′ in mosquito blood, both of which have been described as proliferating hemocytes that express mitotic marker genes [6] , [17] . Likewise, ‘PM6′ in flies mapped well to HC6 in mosquitoes, and both clusters are enriched in genes that encode antimicrobial peptides (AMP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, to demonstrate the power of this feature across species, we compared Drosophila blood marker genes [6] with marker genes derived from A. gambiae (mosquito) blood scRNA-seq [17] . Of note, Drosophila blood cluster ‘PM2′ significantly correlated to ‘HC4′ in mosquito blood, both of which have been described as proliferating hemocytes that express mitotic marker genes [6] , [17] . Likewise, ‘PM6′ in flies mapped well to HC6 in mosquitoes, and both clusters are enriched in genes that encode antimicrobial peptides (AMP).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, ‘PM6′ in flies mapped well to HC6 in mosquitoes, and both clusters are enriched in genes that encode antimicrobial peptides (AMP). In addition, the ‘HC1′ cluster identified in the mosquito blood study maps to mature crystal cell cluster ‘CC2′, and both express high mRNA levels of prophenoloxidases (PPO), which are characteristics of crystal cells or otherwise called oenocytoids [6] , [17] . Interestingly, ‘HC1′ also highly correlated with ‘PM8′, a plasmatocyte cluster that is enriched in peroxiredoxins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phagocytosis might be important to clear viruses from the circulation but, in the midgut, could help virus dissemination. However, recent single cell analyses have indicated that hemocytes are composed of many subgroups that likely have distinct functions in immunity (43)(44)(45)(46). Based on these data, it is possible that epithelial and systemic responses to viral infections mobilize different subtypes of hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…They influence many aspects of the mosquito biology, including reproduction, development, adult survival and, overall, immunity (Coon et al, 2014). The main sites where cellular and humoral components of adult mosquito immunity exert their functions against invaders are the hemocoel with the circulating hemolymph, that contains the immune cells called hemocytes (Hillyer, 2010(Hillyer, , 2016Raddi et al, 2020), and the gut, which receives the sugar and blood meals and that hosts a major component of the insect microbiota (gutassociated microbiota).…”
Section: The Interplay Between Female Mosquito Immune System Gut Microbiota and Vector Competencementioning
confidence: 99%